G223(P) A Novel Neonatal Hospital Record System to improve note keeping for infants admitted to a neonatal unit in a low resource country. (7th April 2014) - Robertson, EJ; Langer, DS; Harrison, C; Lissauer, TJ; Mellor, K; Amos, O
Abstract : Aim: Training and knowledge of specialist neonatal care is frequently limited in low resource countries. We aimed to assess if the introduction of a standardised medical record could improve documentation, assisting nurses and doctors in their approach to daily care of the sick newborn. Method: We gained national approval for the implementation of a novel neonatal medical record. The booklet was divided into sections for admission history, assessment and management, daily ward rounds, growth, prescriptions, investigation results, nursing documentation and discharge information. It was introduced in October 2013, with staff training provided for three weeks. An audit of documentation completeness was performed comparing 30 notes before and one month after the booklet was introduced. Results: Completeness of documentation improved for 7 sections (see Table 1 ). With the new booklet 57% patients had an entry for every day of admission, compared to 23% previously. Growth charts, not previously available, were completed for 50% at admission. Investigation results and discharge planning had not improved. Use by nurses was inconsistent, with many defaulting to the old note format. Conclusion: A standardised neonatal medical record improved documentation by doctors. Nursing documentation was still lacking indicating further teaching and minor amendments to fit local agendas may be required. If improved neonatal outcomes (reduced mortality) are to be observed, full co-operation of staff is required to follow and document daily progress. This is a great quality improvement initiative for a low resource setting, and further assessment is needed after long term use of the document.